Penerapan Model Business Intelligence Pada Perusahaan Retail XLT Untuk Meningkatkan Strategi Pemasaran: PENERAPAN MODEL BUSINESS INTELLIGENCE PADA PERUSAHAAN RETAIL XLT UNTUK MENINGKATKAN STRATEGI PEMASARAN - W . Sulistyoningsih; I Nyoman Yudi Anggara Wiajaya; Helmy Syah Alam (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
Data is something valuable, so PT XLT began to focus on good data processing. Such data includes sales data, purchase data, customer data, and other operational data that are useful for making decisions in determining marketing strategies. Currently, the marketing team in carrying out marketing strategies is only based on intuition and minimal information. Business Intelligence (BI) is one of the solutions for company needs in analyzing and providing information. In this study, researchers will design and build BI dashboards to support marketing strategies at XLT companies. This study aims to apply BI to companies and create reporting dashboards to assist the marketing team in making decisions. The results of this study are to present the information needed by the marketing team in the decision-making process to improve marketing strategies at XLT companies. Decision making is based on the implementation of the marketing mix strategy which contains the 4P components, namely: Price (Price), Product (Product), Place (Distribution), and Promotion (Promotion).